2017
DOI: 10.21037/jtd.2017.06.88
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory support with venovenous extracorporeal membrane oxygenation during stent placement for the palliation of critical airway obstruction: case series analysis

Abstract: Background: Venovenous extracorporeal membrane oxygenation (VV ECMO) is used to support gas transfer of patients suffering from respiratory failure during various procedures. The purpose of this study was to evaluate the technical feasibility and safety of fluoroscopic stent placement under respiratory support with VV ECMO in patients with critical airway obstructions. Methods:We reviewed the records of 17 patients (14 male and 3 female; mean age: 63 years; range, 30-82 years) who underwent self-expandable met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 23 publications
0
25
1
Order By: Relevance
“…Recently, we treated 150 new patients with benign or malignant TBS and performed 400 rigid bronchoscopies in one year. Although we do not use SEMS in any type of TBS due to their disadvantages, some other institutions in South Korea use SEMS in patients with benign TBS as well as those with malignant TBS [20][21][22]. The use of SEMS in patients with benign TBS is controversial, therefore, we retrospectively reviewed the charts of 20 patients who experienced complications with SEMS.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we treated 150 new patients with benign or malignant TBS and performed 400 rigid bronchoscopies in one year. Although we do not use SEMS in any type of TBS due to their disadvantages, some other institutions in South Korea use SEMS in patients with benign TBS as well as those with malignant TBS [20][21][22]. The use of SEMS in patients with benign TBS is controversial, therefore, we retrospectively reviewed the charts of 20 patients who experienced complications with SEMS.…”
Section: Discussionmentioning
confidence: 99%
“…Most of their patients (94.7%) were successfully weaned off ECMO, and death related to complications of ECMO was seen in only one patient. Another report and review of existing literature, 10 noting the apparently good outcome in many reported cases, suggested ECMO for acute severe tracheal obstruction. In another report from Spain, 11 ECMO was used successfully in a case of severe life-threatening airway obstruction due to complications of inflammatory bowel disease.…”
Section: Discussionmentioning
confidence: 98%
“…They verified the feasibility of stent placement under ECMO support but mean survival time was only four months. 6 These unsatisfying results raise questions about the futility of intensive respiratory support, including ECMO and mechanical ventilation.…”
Section: Discussionmentioning
confidence: 99%